Model Sistem Antrean Menggunakan Pola Single Channel-Single Phase Dengan Promodel Pada Antrean SPBU 34.31349 Karawang, Jawa Barat - Anbiya, Muhammad Primasuri; Ibrahim, Ibrahim; Purwani, Ayu Putri (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
This study aims to optimize the queuing system at SPBU 34.41349 Karawang, Jawa Barat by using a single channel-single phase pattern model using ProModel software. An efficient and effective queuing system is essential to minimize customer waiting time and increase customer satisfaction. In this study, analyzed queue data at SPBU 34.41349 to understand the characteristics of queues and modeled them using ProModel.  Identify factors affecting customer wait times and estimate queuing system performance based on simulations performed with ProModel. The results showed that the productivity rate of operators was 96% and the unemployment rate was 4%. This shows that the operator's productivity level is quite good. However, because there is only 1 filling station for motor vehicles, the type of pertalite fuel causes a buildup of queues. Therefore, to reduce queuing time and maximize service is to add one counter on each server which is expected to increase the efficiency and effectiveness of the queuing system at SPBU 34.41349 Karawang, West Java. Keywords: Promodel, Queuing system, Single channel, Statistical test